Building a conducive work environment for teachers through proactive and collaborative conflict management at MA Sirojul Ulum, Krejengan Probolinggo - Ma’arif, Mohamad Ahyar; Kaserero, Subira (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
This study explores conflict management strategies to create a conducive work environment for teachers at MA Sirojul Ulum, Krejengan, Probolinggo. Conflicts in schools, such as interpersonal disagreements and structural role ambiguities, disrupt relationships and reduce teaching effectiveness. Effective conflict management is essential for maintaining harmony and productivity in schools. The research employs a qualitative approach with a case study method, gathering data through in-depth interviews with principals, teachers, and staff, as well as observations and document analysis. The data were analyzed thematically to uncover patterns in conflict dynamics and resolution strategies. The findings indicate that structured deliberations and conflict management training significantly enhance communication and collaboration among teachers, fostering a harmonious work environment. Deliberation provides an open platform for resolving conflicts, while training improves teachers' abilities to handle disputes effectively. However, bureaucratic challenges, such as slow administrative processes, often hinder timely conflict resolution, underscoring the need for streamlined procedures. This research introduces a proactive and collaborative approach to conflict management, which goes beyond reactive strategies. By involving all stakeholders principals, teachers, students, and parents in early identification and resolution of conflicts, this participatory model not only addresses existing issues but also strengthens relationships and supports long-term educational goals. In conclusion, integrating proactive and collaborative conflict management strategies improves teacher performance, enhances the quality of education, and creates a sustainable and productive work environment. These insights provide valuable guidance for school administrators and stakeholders aiming to refine conflict resolution systems in educational settings.